2020
DOI: 10.3390/colloids4010002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bentonite Nanoclay and Cetyltrimethyl Ammonium Bromide Modified Bentonite Nanoclay on Phase Inversion of Water-in-Oil Emulsions

Abstract: The effects of unmodified and modified bentonite nanoclays (with various degrees of surfactant modification) on the catastrophic phase inversion from water-in-oil (W/O) emulsion to oil-in-water (O/W) emulsion were determined experimentally. The bentonite nanoclay (NC-Bt) was suspended in the aqueous phase, and the critical volume fraction of water where phase inversion from W/O to O/W emulsion took place was determined through conductivity measurements. Cetyltrimethyl ammonium bromide (CTAB) was used as a surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Figure 4b shows the surface morphology of bentonite containing MMT which has layered pores that are evenly distributed and no further clumping occurs, this is due to the addition of CTAB surfactant. This study is in line with that carried out by (Ogunlaja & Pal, 2020), who reported that nano bentonite modified with CTAB surfactants could reduce particle agglomeration in the MMT structure.…”
Section: Scanning Electron Microscopy (Sem) Analysis Of Nanobentonite...supporting
confidence: 93%
“…Figure 4b shows the surface morphology of bentonite containing MMT which has layered pores that are evenly distributed and no further clumping occurs, this is due to the addition of CTAB surfactant. This study is in line with that carried out by (Ogunlaja & Pal, 2020), who reported that nano bentonite modified with CTAB surfactants could reduce particle agglomeration in the MMT structure.…”
Section: Scanning Electron Microscopy (Sem) Analysis Of Nanobentonite...supporting
confidence: 93%
“…Table 3 demonstrates that Peak 1 is centered at H = 10.4 nm with the smallest standard deviation (±2.7 nm) and 28% of the intensity of size distribution, being evidence of nanoparticles in the C20A nanoclay used in this work: Peak 2 is centered at H = 361.7 nm with the highest intensity (28.6%) and the highest standard deviation (±28.6 nm). There are several other studies with H like Peak 2, highlighting the H of the organo‐modified MMT nanoclay (between 300 and 400 nm), 63 bentonite nanoclay modified with ammonium bromide (between 100 and 700 nm), 64 and for Cloisite® 30A nanoclay (~300 nm) 51 …”
Section: Resultsmentioning
confidence: 98%
“…Thus far, various methods have been utilized to make the hydrophobicity of bentonite, such as cetyltrimethylammonium bromide (CTAB), polymers (for example, polyethylene), octadecyl dimethyl phenylmethyl ammonium chloride (ODPAC), silanes, and stearic acid (SA) (Hong et al, 2020;Huang et al, 2015;Johansson and Clegg, 2014;Ogunlaja and Pal, 2020;Saki et al, 2020).…”
Section: Introductionmentioning
confidence: 99%